An Example of Neo-Tarekat in Bandung, Indonesia - Muhammad Adlin Sila (Al-Jami'ah: Journal of Islamic Studies, 2009)
At present, several tarekats surfaced in the urban centers of Indonesia and continued to perform as a vehicle of social and cultural cohesion. The emergence of these so-called neo-tarekats (neo-sufi mystical orders) introduced rational reference to the sacred texts and Islamic law and rejected the close association between tarekats and the veneration of saints and holy places as generally known as silsilah in the old version of tarekats. This article depicts a close look at of Tarekat Kadisiyyah, an example of the neo-tarekats, located in central Bandung city of West Java. Most of the followers of this tarekat come from young and educated among urban people in Bandung. mursyid (Ar: murshid) of this tarekat refers to a person named Suprapto Kadis, who experienced the absence of an outward mursyid (lahiriah), but received direct guidance from Allah. There is no chain of transmission of mystical knowledge from a special mursyid to him. This kind of mursyid reminds us the concept of uwaysiyah in classical Islamic literature. Uways is the person who knew the prophet Muhammad but never met him in person. Another concept can be used to analyzes this phenomena is the notions of khidr functioning as an invisible guide for the mursyid. Tarekat Kadisiyyah trained its students that one should become his own self in order to know Allah. In doing this, Tarekat Kadisiyyah concluded that shari‘ah is important as it is the vehicle to gain closeness to Allah.